2013
DOI: 10.4238/2013.december.20.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in the ITS and IGS regions of the ribosomal DNA of Acremonium cavaraeanum exhibiting antimicrobial activity

Abstract: ABSTRACT. Endophytic microorganisms represent promising alternatives for obtaining new drugs of biotechnological importance. In this study, the endophytic species Acremonium cavaraeanum (A1a) isolated from Cocos nucifera was cultivated for the production of secondary metabolites, and its extracts and fractions were evaluated by the dilution method (MIC). The EtOAc extracts and MeOH fractions were tested against Gram-positive and -negative bacteria, and had an MIC of 125 µg/mL when evaluated in the EtOAc extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…It was also reported that Acremonium cavaraeanum from Cocos nucifera has antibacterial activity [15]. It has exhibited antimicrobial activity against Gram-positive bacteria and was inefficient against Gram-negative bacteria [15]. In this paper, the fungal strain Acremonium cavaraeanum CA022 was isolated from the fruiting bodies of an ascomyceteous fungus Shiraia bambusicola, which is known to grow in some provinces south of the Yangtze River of China and in Japan [16].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…It was also reported that Acremonium cavaraeanum from Cocos nucifera has antibacterial activity [15]. It has exhibited antimicrobial activity against Gram-positive bacteria and was inefficient against Gram-negative bacteria [15]. In this paper, the fungal strain Acremonium cavaraeanum CA022 was isolated from the fruiting bodies of an ascomyceteous fungus Shiraia bambusicola, which is known to grow in some provinces south of the Yangtze River of China and in Japan [16].…”
mentioning
confidence: 94%
“…For example, pyrrocidines A from Acremonium zeae presented inhibitory effects on various pathogens [13]. It was also reported that Acremonium cavaraeanum from Cocos nucifera has antibacterial activity [15]. It has exhibited antimicrobial activity against Gram-positive bacteria and was inefficient against Gram-negative bacteria [15].…”
mentioning
confidence: 99%
“…Chemical and pharmaceutical studies on Acremonium spp. have proven that they are also prolific producers of other secondary metabolites including steroids, terpenoids, metroterprnoids, polyketides, alkaloids and peptides [ [5] , [6] , [7] ]. However, the vast majority of the biosynthetic machinery of those metabolites as well as physiological and biochemical effectors of this genus are still obscure.…”
Section: Introductionmentioning
confidence: 99%